2022
DOI: 10.1002/ecm.1516
|View full text |Cite
|
Sign up to set email alerts
|

Imprints of latitude, host taxon, and decay stage on fungus‐associated arthropod communities

Abstract: Interactions among fungi and insects involve hundreds of thousands of species. While insect communities on plants have formed some of the classic model systems in ecology, fungus-based communities and the forces structuring them remain poorly studied by comparison. We characterize the arthropod communities associated with fruiting bodies of eight mycorrhizal basidiomycete fungus species from three different orders along a 1200-km latitudinal gradient in northern Europe. We hypothesized that, matching the patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 111 publications
0
10
0
Order By: Relevance
“…While arthropods feeding on fungal fruiting bodies are rarely specialized on particular host species, many fungivores feed on sets of related fungal hosts (Orledge and Reynolds 2005, Põldmaa et al 2016, Koskinen et al 2019. Such cladelevel specificity was also revealed by Koskinen et al (2022), who found the overall similarity of arthropod communities to decrease with an increasing phylogenetic distance among fungal hosts. For consumers specializing on particular fungal taxa or clades, non-random responses of entire fungal clades to spatiotemporal variation in environmental conditions will therefore introduce further unpredictability in resource availability: not only are fruiting bodies as such short-lived and patchily distributed, but the occurrence and abundance of entire host groups is further clumped in time and space.…”
Section: Phylogenetic Signal In the Assembly Of Fungal Fruiting Body ...mentioning
confidence: 88%
See 3 more Smart Citations
“…While arthropods feeding on fungal fruiting bodies are rarely specialized on particular host species, many fungivores feed on sets of related fungal hosts (Orledge and Reynolds 2005, Põldmaa et al 2016, Koskinen et al 2019. Such cladelevel specificity was also revealed by Koskinen et al (2022), who found the overall similarity of arthropod communities to decrease with an increasing phylogenetic distance among fungal hosts. For consumers specializing on particular fungal taxa or clades, non-random responses of entire fungal clades to spatiotemporal variation in environmental conditions will therefore introduce further unpredictability in resource availability: not only are fruiting bodies as such short-lived and patchily distributed, but the occurrence and abundance of entire host groups is further clumped in time and space.…”
Section: Phylogenetic Signal In the Assembly Of Fungal Fruiting Body ...mentioning
confidence: 88%
“…One type of communities on which phylogenetic signatures remain poorly known (Abrego et al 2022, Bässler et al 2022) are local assemblages of fungal fruiting bodies. This constitutes an important knowledge gap because fungal fruiting bodies provide a resource for a plethora of organisms (Hanski 1989, Osawa et al 2011, Kurina et al 2015, Koskinen et al 2019, 2022). Fungus‐based trophic networks are highly diverse even in the boreal and temperate zones, where thousands of fungal species produce macroscopic fruiting bodies (Salo et al 2005, Mueller et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As technology advances, researchers can utilize new cost-effective and efficient ways to identify invertebrates in sporocarps. The shift away from traditional rearing techniques to DNA metabarcoding will enhance our understanding and give us new insights into this subfield [ 104 , 105 , 106 , 107 , 108 , 109 ].…”
Section: Discussionmentioning
confidence: 99%